Evaluation of biological activities of polysaccharides and compounds isolated from Lentinus edodes - Hong Ha, Tran Thi; Chinh, Luu Van; Cuong, Le Huu; Nhu Hang, Tran Thi; Nghi, Do Huu; Hung, Truong Ngoc; Nga, Nguyen Thi; Huong, Le Mai (Academia Journal of Biology, 2013)
Two polysaccharide samples (Poly1 and Poly2) and three compounds (galactiol, ergosterol and ergosterol peroxide) were isolated from the fruiting body of Lentinus edodes. Poly1 and ergosterol peroxide (NH-3) showed cytotoxicities against two liver cancer cell lines Hep-G2 (Hepatocellular carcinoma) and RD (Rhabdomyosarcoma) with IC50 values of 29.62 and 34.24; 3.84 and 7.61 mg/mL respectively. Poly1 and NH-3 showed capacities for decreasing Hep-G2 tumor density by 54.09 and 58.33%, respectiviely in comparison to the control. In addtion, the average sizes of tumors treated with Poly1 and NH-3 were decreased by 35.36 and 55.18%, respectively as compared to the control.